De-tooling technology: networked computing as an environment, purpose and medium for social action. - Allen, Matthew (NA, 2009)
This keynote presentation begins with a contrast. On the one hand, network technologies are very desirable for social action, allowing activists to achieve more with less, more quickly and with broader impact. They are tools which help greatly. On the other, the very advantages they bring are bound up with the cultural logic of contemporary capitalism, obsessed as it is with squeezing increased productivity from every last resource at its disposal - natural or artificial, human or otherwise. This contrast alerts us to the need to look beyond network technologies as the easy solution to every problem, and focus instead on the human relationships which might be enabled by them, but for which technology never completely account. As the remainder of the presentation will outline, this focus on relationships requires us to 'de-tool' information technology: to think of it as something other than a fix for problems to be picked up and put down at will. Rather, it is more valuable to think of networked computing as part of the environment within which social action can occur; often an important purpose for social action; and as a medium which nutures expression and engagement of self and belief. Ultimately, there is only a fine line between exploiting technology and exploiting people: social action in a network society can avoid stepping over this line by recognising the symbiosis of people and computers that together enables us to work productively for change and development.